Decolonizing Global History? A Latin American Perspective (2020)
The field of global history has been thriving for over two decades; however, unlike Europe, the United States, and Asia, which have witnessed a true “boom” in this area, there has been no such significant development in Latin America. In fact, there is even an attitude of rejection toward what many academics in the region consider an “Anglo-Saxon trend.” This article argues that this lack of attachment to global history lies in conceptual flaws, as well as in the continuous production of academic work that lacks nuance and is predominantly based on secondary literature written in English. To counteract these tendencies and better adapt the field to the academic and historical realities of Latin America, this article engages in a dialogue with representatives of decolonial studies. This article suggests that an approach to this movement—whose followers condemn the implicit Eurocentrism of Western historiography—will contribute to the necessary decolonization of global history.